Severidade de ocorrência de mancha de septória e produtividade do girassol irrigado - Radons, Sidinei Zwick (2010)
This study aimed to evaluate the severity of occurrence of septoria leaf spot in sunflower, its association with meteorological variables and its effect on yield of field irrigated sunflower. The experiments were conducted in Santa Maria - RS during the 2008 spring season and during the 2009 fall growing season, with sowings in September and in February, respectively. Observations of severity of septoria leaf spot were made throughout the crop cycle, and with a disease forecasting system different times for fungicide applications have been identified. Results show that a sequence of rainy days, with favorable temperatures to the pathogen, tend to contribute to the development of septoria leaf spot in sunflower. In contrast, when water needed by plants is restored by irrigation, even temperature is favorable to the pathogen, disease development rate is lower than during and within 10 days of rainy periods. There were observed differences in septória leaf spot severity between treatments with and without fungicide application, but were not related to the yield of sunflower achenes. Fungicide application according to the different treatments did not significantly affect achene yield either. Therefore, significant differences in the variables that represent the progression of the disease do not necessarily imply in significant differences in yield.